‘Why Are the White Kids Clean and the Brown Kids Still Dirty?’: Parental Encounters with Racial Discrimination in Early Childhood Services - Cherie Suzanne Lamb (Social Sciences)
In Australia, the Early Years Learning Framework sets out a vision for all children to experience belonging, wellbeing, confidence, and a sense of identity. This article forefronts the voices of parents with refugee experience, through focus groups and interviews, to explore why they removed their children from early childhood education and care (ECEC) services. Supplemented by interviews with early childhood practitioners and researcher experience, constructivist grounded theory overlaid with critical race theory provided a lens through which to scrutinize the way racism implicitly impacts structural practices within ECEC environments. The overarching message was that everything is framed within the parameters of the dominant culture, which was taken for granted by educators, who are predominantly White and middle class. Parents withdrew their children because they perceived care to be culturally unsafe and unsuitable and because cultural and linguistic support was rarely available. Of concern were the smothering effects of assimilation and the imposition of a foreign culture which unsettled family life. Compromised identity and the nullification of cultural and linguistic heritage left children with little or no sense of belonging.